Kinetic, Isotherm And Equilibrium Study Of Adsorption Of Hydrogen Sulfide From Wastewater Using Modified Eggshells - Habeeb, Omar Abed; K., Ramesh; Ali, Gomaa A. M.; R. M., Yunus; Olalere, Olusegun Abayomi (IIUM, 2017)
The studies of adsorption equilibrium isotherm and kinetics of hydrogen sulfide-water systems on calcite-based adsorbents prepared from eggshell are undertaken. The effects of operating variables such as contact time and initial concentration on the adsorption capacity of hydrogen sulfide are investigated. The modified eggshells are characterized by using different analytical approaches such as Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR). The batch mode adsorption process is performed at optimum removal conditions: dosage of 1 g/L, pH level of pH 6, agitation speed of 150 rpm and contact time of 14h for adsorbing hydrogen sulfide with an initial concentration of 100-500 mg/L. In the current study, the Langmuir, Freundlich, Temkin, and Dubinin models are used to predict the adsorption isotherms. Our equilibrium data for hydrogen sulfide adsorption agrees well with those of the Langmuir equation. The maximum monolayer adsorption capacity is 150.07 mg/g. Moreover, the kinetics of H2S adsorption by using the modified calcite of eggshell follows a pseudo-second-order model. From the current work, we have found that the calcite eggshell is a suitable adsorbent for H2S embeded inside the waste water. Most importantly, chicken eggshell is a waste and vastly available; hence, it could serve as a practical mean for H2S adsorption.